2019
DOI: 10.18203/2320-6012.ijrms20190935
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices of medical students about self-medication for acne

Abstract: Background: Acne is most prevalent in adolescent girls. Self-medication for acne is most common in medical students. This study was done to evaluate the knowledge, reason, perception and pattern of self-medication for acne among undergraduate medical students.Methods: A cross-sectional study included medical students of the second phase and final phase (part I and part II). A pretested questionnaire was given to them which included questions on knowledge, attitude and practice about self-medication for acne.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Acne is a very common skin condition affecting teenagers and adolescents worldwide. The prevalence of acne in our setup was found to be 69.9%, which was consistent with the findings of Talanikar et al [7]. Comparably, a study conducted in Karachi showed a prevalence of 55.9% among the students [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Acne is a very common skin condition affecting teenagers and adolescents worldwide. The prevalence of acne in our setup was found to be 69.9%, which was consistent with the findings of Talanikar et al [7]. Comparably, a study conducted in Karachi showed a prevalence of 55.9% among the students [8].…”
Section: Discussionsupporting
confidence: 92%
“…The most common reason for self-medication in our study was the mildness of the condition (34.3%), followed closely by easy availability (30.1%). The mild nature of the disease has been reported as the most common reason in many studies [6-7]. Acquaintances (seniors/friends/members of the family) were the most frequently cited source of information in our study (55.8%).…”
Section: Discussionmentioning
confidence: 62%
“…The published works on self-medication in Dermatology are scarce 5,6,[14][15][16][17] and those that focus on self-treatment among healthcare professionals are even less numerous. 2,3,[18][19][20][21] A systematic review published in 2014 about selftreatment of skin lesions in the general population showed a variable prevalence, which ranged between 6% and 68% in the different studies. 5,6 Other studies not included in this systematic review also focusing on the self-treatment of different concrete dermatoses in the general population obtained higher percentages of selfmedication, although they oscillated in a wide range, between 33% and 77%.…”
Section: Discussionmentioning
confidence: 99%
“…In those articles, selftreatment prevalence was between 50% and 77%. 2,3,[19][20][21] It should be noted that these studies included cosmetic products, medicinal herbs and other home remedies and alternative medicines that were excluded in our survey. In fact, these nonpharmacological medicines were used by a significant number of the medical students evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation